2019
DOI: 10.1128/jb.00686-18
|View full text |Cite
|
Sign up to set email alerts
|

RNase HIII Is Important for Okazaki Fragment Processing in Bacillus subtilis

Abstract: RNA-DNA hybrids are common in chromosomal DNA. Persistent RNA-DNA hybrids result in replication fork stress, DNA breaks, and neurological disorders in humans. During replication, Okazaki fragment synthesis relies on frequent RNA primer placement, providing one of the most prominent forms of covalent RNA-DNA strands in vivo. The mechanism of Okazaki fragment maturation, which involves RNA removal and subsequent DNA replacement, in bacteria lacking RNase HI remains unclear. In this work, we reconstituted repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(90 citation statements)
references
References 47 publications
2
88
0
Order By: Relevance
“…To assay for RNase H activity, we used an oligonucleotide labeled with an IR dye at the 5′ end that contained four embedded rNMPs flanked by DNA on either side. This labeled oligonucleotide was annealed to a complementary DNA strand, creating a double‐stranded RNA‐DNA chimeric substrate as previously described (Randall et al ., 2019). We used this approach because prior work showed that bacterial RNase HI, HII, and HIII are all active on this substrate (Ohtani et al ., 1999a; Randall et al ., 2017; Randall et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assay for RNase H activity, we used an oligonucleotide labeled with an IR dye at the 5′ end that contained four embedded rNMPs flanked by DNA on either side. This labeled oligonucleotide was annealed to a complementary DNA strand, creating a double‐stranded RNA‐DNA chimeric substrate as previously described (Randall et al ., 2019). We used this approach because prior work showed that bacterial RNase HI, HII, and HIII are all active on this substrate (Ohtani et al ., 1999a; Randall et al ., 2017; Randall et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…RNA‐DNA hybrids in the form of Okazaki fragments and DNA polymerase errors are similar in that the RNA is covalently linked to DNA through a phosphodiester bond (Randall et al ., 2017; Randall et al ., 2019). Another prevalent RNA‐DNA hybrid forms during transcription when mRNA transcripts are base‐paired with the transcribed DNA strand, displacing the coding strand as ssDNA to form an R‐loop [for review (Schroeder et al ., 2015)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the major roles played by DNA2 in eukaryotic organisms are apparently already provided by other enzymes in bacteria. For example, the AddAB- and RecBCD-type helicase–nucleases are responsible for DNA end resection to promote homologous recombination ( 15 ), and Okazaki fragments are processed by RNaseH ( 41 ), although the latter process remains poorly understood in bacteria ( 42 ). Finally, Bad proteins all contain a central conserved domain that is not present in any eukaryotic DNA2 protein ( Supplementary Figures S1-S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…RecBCD-type helicase-nucleases are responsible for DNA end resection to promote homologous recombination (15), and Okazaki fragments are processed by RNaseH (39), although the latter process remains surprisingly poorly understood in bacteria (40). Finally, Bad proteins all contain a central conserved domain that is not present in any eukaryotic DNA2 protein (Supplementary Figures 1-3).…”
Section: Discussionmentioning
confidence: 99%